Efektivitas Latihan Aerobik yang dikombinasikan dengan Fisioterapi dalam Menurunkan Risiko Cedera pada Orang dengan Obesitas - Rezki Amalia Nurshal; Sherly Mutiara; Fauzan Agus Santoso (JURNAL RISET RUMPUN ILMU KEDOKTERAN, 2023)
This study aims to evaluate the effectiveness of aerobic exercise combined with physiotherapy in reducing injury risk among individuals with obesity. Obesity is a global health issue that significantly increases the risk of injuries, particularly within the musculoskeletal system. The research employed an experimental design with pre-test and post-test, involving 40 obese participants divided into two groups: an intervention group that underwent a 12-week program combining aerobic exercise and physiotherapy, and a control group that received no intervention. The intervention program included aerobic exercises designed to improve cardiovascular endurance and flexibility, alongside physiotherapy sessions focused on muscle strengthening and balance enhancement. The results showed that the intervention group experienced a significant reduction in injury risk and improvement in physical abilities compared to the control group (p < 0.05). Additionally, participants in the intervention group reported reduced pain levels and improved quality of life. These findings indicate that the combination of aerobic exercise and physiotherapy is effective in mitigating injury risks for individuals with obesity. This study provides valuable insights for healthcare practitioners in designing better rehabilitation programs for obese populations and encourages individuals to actively participate in safe and effective exercise regimens.